An evaluation of scheduling techniques using simulation for a herb manufacturing company [electronic resource] - 455294 Kamaruizani Abdul Manaf (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2008